The Synthesis, Characterization, Crystal Structure and Photophysical Properties of a New Meso-BODIPY Substituted Phthalonitrile - Sen, Pinar; Atmaca, Goknur Yasa; Erdogmus, Ali; Dege, Necmi; Genc, Hasan; Atalay, Yusuf; Yildiz, S. Zeki (SPRINGER/PLENUM PUBLISHERS, 2015)
A new highly fluorescent difluoroboradipyrromethene (BODIPY) dye (4) bearing an phthalonitrile group at meso-position of the chromophoric core has been synthesized starting from 4-(4-meso-dipyrromethene-phenoxy)phthalonitrile (3) which was prepared by the oxidation of 4-(2-meso-dipyrromethane-phenoxy)phthalonitrile (2). The structural, electronic and photophysical properties of the prepared dye molecule were investigated. The final product exhibit noticeable spectroscopic properties which were examined by its absorption and fluorescence spectra. The original compounds prepared in the reaction pathway were characterized by the combination of FT-IR, H-1 and C-13 NMR, UV-vis and MS spectral data. It has been calculated; molecular structure, vibrational frequencies, H-1 and C-13 NMR chemical shifts and HOMO and LUMO energies of the title compound by using B3LYP method with 6-311++G(dp) basis set, as well. The final product (4) was obtained as single crystal which crystallized in the triclinic space group P-1 with a = 9.0490 (8) , b = 10.5555 (9) , c = 11.7650 (9) , alpha = 77.024 (6)angstrom, beta = 74.437 (6)angstrom, gamma = 65.211 (6)angstrom and Z = 2. The crystal structure has intermolecular C-H center dot center dot center dot F weak hydrogen bonds. The singlet oxygen generation ability of the dye (4) was also investigated in different solvents to determine of using in photodynamic therapy (PDT).
Keywords: Bodipy; Synthesis; Crystal structure; Phthalonitrile; Fluorescence; Electronic spectra; photodynamic therapy; SPECTROSCOPIC PROPERTIES; MOLECULAR-STRUCTURE; DERIVATIVES; DYES; Biochemistry & Molecular Biology; Chemistry